PENGARUH BEBAN KERJA, KOMPENSASI FINANCIAL DAN KOMPENSASI NON FINANCIAL TERHADAP KINERJA KARYAWAN (STUDI KASUS BAGIAN PRODUKSI PT. DARMASINDO INTIKARET TEBING TINGGI) - Hutauruk, Vivi Natalia; Tinambunan, Anitha Paulina (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to determine the effect of workload , financial compensation and non financial compensation on the performance of production employees at PT.Darmasindo Intikaret Tebing Tinggi.The total population of this study is 60 people and the number of samples through the census is 60 people.The analysis technique used in this study is multiple liner regression.Descrptive analysis and hypothesis testing.he results of this study indicate that the variable workload,financial compensation,nonfinancial compensation have a positive and significant effect on the performance of employees in production division of PT.Darmasindo Intikaret Tebing Tinggi